The garden - Matas, Carol, 1949- (New York : Simon & Schuster Books for Young Readers, 1997)
After leading a group of Jewish refugees to Israel after World War II, sixteen-year-old Ruth joins the Haganah, the Jewish Army, and helps her people fight to keep the land granted to them by the United Nations.
810
810
Keywords: Israel-Arab War, 1948-1949 -- Juvenile fiction; Jews -- Israel -- Juvenile fiction; Israel-Arab War, 1948-1949 -- Fiction; Jews -- Israel -- Fiction; Israel -- Fiction